A cross-sectional study investigating the relationship between urinary albumin creatinine ratio and abdominal aortic calcification in adults - Xue, Xian; Li, Chen; Chen, Dongping (Frontiers in Cardiovascular Medicine, 2024)
The presence of abdominal aortic calcification (AAC) is strongly linked to the development of atherosclerosis and the incidence of morbidity and mortality related to cardiovascular diseases (CVD).Urinary albumin creatinine ratio (UACR) was found related with the increased risk of CVD. The aim of this study is to explore the relationship between the UACR and severe AAC (SAAC). This study included a total of 2379 individuals aged over 40 years, and their information was obtained from the National Health and Nutrition Examination Survey conducted(NHANES) in 2013-2014.The measurement of AAC was conducted through dual-energy X-ray absorptiometry and assessed using the Kauppila scoring system. Severe SAAC was characterized by a Kauppila score of 6 or higher. Multivariate regression models were used to analyze the relationship between UACR level and SAAC, with covariate adjustment. In the completely adapted model, the top third subgroup exhibits increased likelihood of severe AACSAAC (odds ratio 1.50; 95%CI 0.98, 2.29; p=0.030) in contrast to the bottom third subgroup. The subgroup analyses revealed a more pronounced correlation among the older participants (p-value for interaction = 0.013).In the United States, severe AACSAAC was more likely to occur in adults who had a higher probability of UACR. The use of UACR has the potential to be a valuable method for forecasting the likelihood of SAAC.